Nurse managers’ early intervention in nurses’ professional conduct: A document analysis - Papinaho, Oili (Sage, 2025)
Nurses’ professional conduct and work-related well-being are crucial for providing high-quality, safe patient care. Previous knowledge about nurse managers’ early interventions in nurses’ professional conduct is scarce. The aim of this study was to describe how nurse managers intervene in registered nurses’ professional conduct, based on the documents of early intervention and support. A retrospective, cross-sectional document analysis with inductive content analysis was conducted on 43 documents of an early intervention and support program for registered nurses in one Finnish hospital between 2019 and 2021. The manuscript and reporting of the findings were guided by the Standards for Reporting Qualitative Research checklist. The concerns about nurses’ work-related well-being and their working initiated the early intervention process. Nurse managers’ early interventions included supportive and strength-based approaches. These involved appreciating the nurses’ own awareness of their ability to work and supported the process, as did a collaboration with occupation health and other support services. More knowledge is needed about the influence of early intervention programs and nurses' and managers' awareness of different methods.